THE ROLE OF THE UNIVERSITY FOR THE HUMANITIES IN SOLVING SOCIAL AND FOREIGN POLICY PROBLEMS - Alexandr V. Gushchin; Aleksandr S. Levchenkov (Moscow Polytechnic University, 2017)
The article focuses on the role of modern university for the humanities in the implementation of the important tasks in the field of enlightenment, social support, strengthening the role of the university in the implementation of the policy of «soft power» in Russia. The authors also explore the potential of the modern university in the development of public diplomacy. The particular emphasis is made on the important role of the development of cooperation between modern university and public authorities and interstate integration associations in the Eurasian space, taking into account the experience of RSUH in this field.